TERAZOSIN EVALUATION AS MALE LUTS TREATMENT USING IPSS SUB-SCORING RATIO - Tanggo, Christian Ronald K.; Safriadi, Ferry (Indonesian Urological Association, 2013)
Objective: To evaluate the improvement of Lower Urinary Tract Symptoms (LUTS) in males treated with terazosin based on sub scoring ratio of the International Prostatic Symptoms Score (IPSS). Material & Method: Sixty eight male with LUTS subjected to terazosin 1 mg daily and divided into two groups based on IPSS sub scoring ratio. After 3 months improvement of the symptoms were evaluated using the IPSS. Data analysis was done using paired T-test. The conclusion was based on significance level p<0,05. Results: The IPSS score was improving on both failure to void group (IPSS- v/s >1) and failure to store group (IPSS- v/s ≤1) after 3 months of Terazosin therapy (mean= 9,56 versus 6,94). Statistically superior improvement was observed on failure to voiding group (p=0,0003) (95CI:1,30-3,93). Conclusion: Terazosin is best given to male LUTS with IPSS- v/s >1 although both groups respond well.Keywords:International prostatic symptoms score, sub score, failure to voiding, failure to storage, male, lower urinary tract symptoms.